Pembiasaan Membaca Al-Qur’an sebelum Kegiatan Belajar Mengajar di SD Swasta Islam El-Hanan: Studi Deskriptif selama Kegiatan Magang (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to describe the implementation of the Quranic recitation habit before teaching and learning activities and the role of students in supporting Quranic learning activities during the internship. Quranic recitation habit is one of the school's flagship programs, aiming to instill a love of the Quran, develop religious character, and establish a Quranic learning environment for students from an early age. This study used a descriptive method with a qualitative approach. Data collection techniques were conducted through observation, interviews, and documentation during the internship. Observations were made through direct observation of Quranic recitation, memorization, muraja'ah (recitation), and moral development activities for students before the teaching and learning activities began. The results showed that the Quranic recitation habit before teaching and learning activities had a positive impact on students, including improving discipline, calmness in learning, and fostering a love of the Quran. Furthermore, student involvement in the internship contributed to supporting the Quranic learning process through memorization assistance, tahsin guidance, and moral development. Internships also provide students with practical experience in developing their academic, professional, and spiritual competencies as future educators. Thus, cultivating the habit of reciting the Quran before teaching and learning activities can be an effective means of developing a Quranic generation with noble morals and Islamic character.